Pengaruh Eksistensi UNSRAT dan Perkembangan Kota Manado Terhadap Permukiman di Sekitar Kampus - Rico Londah (Universitas Sam Ratulangi, 2020)
The capital of the province of North Sulawesi, Manado City is classified as a middle city, in terms of population. The city of Manado has become a destination city for the inhabitants of the surrounding area in fulfilling the necessities of life, both work, education, and health. Sam Ratulangi University (UNSRAT) Manado, is the largest campus in the city of Manado. Related to this problem, there are two problems identified as follows: The existence of the UNSRAT Campus brings benefits to the surrounding community, this causes the development of the environment around the campus to be out of control. Furthermore, due to the development of the campus, population growth and surrounding settlements are growing rapidly, this condition causes the environment to become less beautiful. The method used is a qualitative descriptive method. The data used in this study are primary and secondary data. Primary data collection is carried out through: Direct observation /observation, interviews with research resource persons, mapping the area and running a questionnaire. Secondary data obtained through agencies include sub-district and kelurahan maps, and micro maps (map of research locations and maps of existing buildings and areas). The research area is divided into four sections namely North, East, South and West Site. There are several aspects that become the focus of this research, those aspects are the Housing Settlement Aspect; Generally, the surrounding population is affected by the existence of the UNSRAT campus itself, but there are also those who have reasons: close to the workplace, close to children's education facilities, a comfortable environment. For the residential aspect, boarding houses thrive with additional patterns: rooms, new buildings, and dormitory construction. Infrastructure Aspects and Environmental Infrastructure; has complete infrastructure such as electricity networks, clean water, roads, sidewalks, landfills. Having supporting facilities, both on campus and outside campus such as health facilities, worship facilities, primary and secondary education facilities, sports facilities and other facilities. Legal Aspects and Area Management; The average land ownership is already certified, although it has not yet taken into account the building boundary factors. Socio-Economic Aspects; In the study site has 1116 boarding houses with a pattern of growing houses, and dozens of Student Dorms. Citizenship Services Business is a positive thing felt by the people around the existence of the UNSRAT Campus. The existence of the UNSRAT Campus brings benefits to the surrounding community, this has caused the development of the environment around the campus to be out of control. This can be seen by the mushrooming of boarding houses and businesses around the residents. Residents of boarding rooms are no longer dominated by students, but also has been inhabited by various groups. The mushrooming of boarding houses and student dormitories, responded by residents of the settlement as a business opportunity. Criminal cases that occur in the campus environment are a bad influence of the residential environment on the UNSRAT campus, and try to be overcome by the UNSRAT by building a parapet around the campus. Keywords: Manado City, UNSRAT, Settlements Around the Campus